TEACHING READING COMPREHENSION OF ENGLISH THROUGH COMMUNICATIVE APPROACH IN HIGHER EDUCATION (Conferencea, 2023)
The objectives of this study are to investigate the perceptions of the secondary homeschooling students on the use of the communicative approach (CLT) in their reading classrooms and to find out to what extent CLT contributes to the development of ESL learners’ reading skill. Four procedures were employed for data collection which included Pre-test and Post-Test, Classroom Observation, Questionnaire and Structured Interview. In general, the results in the Experimental Group showed that there was significant improvement among the learners between pre and post-test scores. Therefore, we can conclude that there was a significant improvement in scores between pre-test to post-test scores. Most secondary homeschooling students are enthusiastic and positive about the communicative approach in their ESL reading classrooms, whereby they learn more vocabulary through group discussions and improve their reading comprehension when exchanging ideas and opinions. Responses and attitude were very positive and strongly agreed with the use of CLT for improving their reading skills as the CLT approach has changed the reading class atmosphere to be better than before. Therefore, the homeschooling students felt pretty cheerful, comfortable and excited during the learning process of reading using CLT activities. Besides that, both homeschooling teachers tend to have a clear, positive and supportive attitudes and perceptions toward CLT. They strongly agreed that CLT is an effective and useful teaching method to accommodate the demands of the time as this method put high emphasis on the interpersonal skill, stimulate the students to communicate their enthusiasm as well as stimulate their interest in their language learning process. Moreover, this approach is advantageous and favourable as the approach is to involve every student in the communicative activities and places high emphasis on communication which highly encouraged the students to communicate and interact with each other as well as stimulate their interest in English learning and developing their learner autonomy